Analysis of Thickness, WVTR, and Microstructure of Whey-Gelatin Protein Based Film with Variation in Chia Seed (Salvia hispanica L.) Concentration - Fitrah, Qifyanti; Fahrullah, Fahrullah (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Edible film is a thin film that can be eaten or consumed directly and serves as a barrier to water vapour, light, gas, fat, and other solutes. Edible film has biodegradable properties that reduce environmental damage. The purpose of this study was to determine the effect of chia seed addition with different concentrations on the thickness, water vapour transmission rate (WVTR), and microstructure of protein-whey gelatin-based edible film. The study employed a completely randomized design comprising three treatments and three replicates. The treatments comprised the addition of chia seeds at different concentrations, namely C1 (0.05 ml), C2 (0.10 ml) and C3 (0.15 ml). The collected data were analysed using Analysis of Variance (ANOVA), with significant differences being followed by Duncan Multiple Range Test (DMRT). In addition, microstructure measurements were analysed descriptively. The addition of different concentrations of chia seeds resulted in a significant difference (P < 0.01) in the thickness value of whey-gelatin protein-based edible films, but no difference (P > 0.05) in the WVTR of whey-gelatin protein-based edible films. The study produced edible films with thickness values of 0.294–0.304 mm, WVTR of 4.57–5.41 g/mm²/day. The use of chia seed at a concentration of 0.10 ml produces a film with good thickness and WVTR values in comparison to other treatments. The resulting thickness value is 0.302 mm, while the WVTR is 4.57-5.41 g/mm²/day. Furthermore, the film microstructure is denser and more uniform.